2010
DOI: 10.1063/1.3290251
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric accelerometers for ultrahigh temperature application

Abstract: High temperature sensors are of major importance to aerospace and energy related industries. In this letter, a high temperature monolithic compression-mode piezoelectric accelerometer was fabricated using YCa4O(BO3)3 (YCOB) single crystals. The performance of the sensor was tested as function of temperature up to 1000 °C and over a frequency range of 100–600 Hz. The accelerometer prototype was found to possess sensitivity of 2.4±0.4 pC/g, across the measured temperature and frequency range, indicating a low te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 99 publications
(60 citation statements)
references
References 17 publications
0
60
0
Order By: Relevance
“…In comparison with capacitive and piezoresistive accelerometers, piezoelectric accelerometers exhibit a wide operating frequency range, as well as cost-efficiency, stability, rapid response, ease of integration, and excellent repeatability [3,62,63]. Piezoelectric accelerometers are usually non-resonant sensors, with the operation frequency lower than the fundamental resonant frequency.…”
Section: Relaxor-pt Accelerometersmentioning
confidence: 99%
“…In comparison with capacitive and piezoresistive accelerometers, piezoelectric accelerometers exhibit a wide operating frequency range, as well as cost-efficiency, stability, rapid response, ease of integration, and excellent repeatability [3,62,63]. Piezoelectric accelerometers are usually non-resonant sensors, with the operation frequency lower than the fundamental resonant frequency.…”
Section: Relaxor-pt Accelerometersmentioning
confidence: 99%
“…These crystals show the merits of high melting points (1400-1700 °C) and high effective piezoelectric coefficients d eff (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) pC/N) [20][21][22][23][24][25][26]; the evaluations of the temperature dependence of dielectric, piezoelectric and electromechanical properties, however, are limited. Of particular significance is that the monoclinic rare-earth calcium oxyborate crystals (ReCa 4 O(BO 3 ) 3 , ReCOB, Re: rare earth), which have been extensively investigated for nonlinear optical applications in the last two decades [27][28][29][30][31][32][33], were reported to exhibit good piezoelectric properties and high electrical resistivity at an elevated temperature of 1000 °C, with no phase transition prior to their melting points (~1400-1520 °C) [1][2][3][34][35][36][37][38]. Table 1 summarizes the basic characteristics of various high temperature piezoelectric crystals in monoclinic, trigonal and tetragonal systems, where the monoclinic ReCOB crystals were found to exhibit relatively high melting points, as well as relatively large piezoelectric coefficients, promising high temperature piezoelectric sensor applications.…”
Section: Open Accessmentioning
confidence: 99%
“…Compared with the commercial strain gauge and optical fiber sensors, etc., piezoelectric sensors have greater potentials in realizing high temperature (>600 °C) sensing with the merits of high accuracy, fast response time and ease of integration [1][2][3][4].…”
Section: Open Accessmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15] Among these crystals, NdCOB crystals were reported to possess a relatively high surface acoustic wave (SAW) coupling factor (k 2 = 0.8%) and low linear temperature coefficient of delay (TCD) (close to zero), 16 while YCOB crystals were observed to show high stability of electromechanical properties at elevated temperatures, 14,15 and explored for high temperature accelerometer applications. [17][18][19] In previous reports, it has been revealed that the piezoelectric coefficient d 26 and electromechanical coupling factor k 26 increase with increasing rare-earth ionic radius, the relationship between crystal structure and piezoelectric properties was established, where the distortions of Re-O and Ca-O octahedra in ReCOB crystals were believed to account for the enhancement of piezoelectric coefficient d 26. 20-22 However, among ReCOB crystals, reports on the growth and structure of PrCOB crystals are very limited.…”
Section: Motivationmentioning
confidence: 99%